2011
DOI: 10.1242/jeb.047407
|View full text |Cite
|
Sign up to set email alerts
|

Flowers help bees cope with uncertainty: signal detection and the function of floral complexity

Abstract: SUMMARYPlants often attract pollinators with floral displays composed of visual, olfactory, tactile and gustatory stimuli. Since pollinators' responses to each of these stimuli are usually studied independently, the question of why plants produce multi-component floral displays remains relatively unexplored. Here we used signal detection theory to test the hypothesis that complex displays reduce a pollinator's uncertainty about the floral signal. Specifically, we asked whether one component of the floral displ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
105
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(113 citation statements)
references
References 54 publications
2
105
0
2
Order By: Relevance
“…These findings suggest that the benefits of bimodal guides may not relate to NDTs. Previous studies have shown that displays incorporating compound signals reduce uncertainty (Leonard et al 2011a;Riffell and Alarcón 2013) and enhance decision making (Kulahci et al 2008), although these benefits from multimodal displays relate to pre-landing choices compared to the post-landing nectar discovery speeds investigated in this study. Our findings also suggest that the time benefits of non-radiating nectar guides are comparable, at least with the patterns used here, to radiating guides.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…These findings suggest that the benefits of bimodal guides may not relate to NDTs. Previous studies have shown that displays incorporating compound signals reduce uncertainty (Leonard et al 2011a;Riffell and Alarcón 2013) and enhance decision making (Kulahci et al 2008), although these benefits from multimodal displays relate to pre-landing choices compared to the post-landing nectar discovery speeds investigated in this study. Our findings also suggest that the time benefits of non-radiating nectar guides are comparable, at least with the patterns used here, to radiating guides.…”
Section: Discussionmentioning
confidence: 68%
“…Nectar guides are thought to benefit both plants and their pollinators through reductions in nectar discovery time (NDT) and the likelihood of nectar robbing as well as increasing accuracy and pollen export (Waser and Price 1983;Leonard et al 2011aLeonard et al , 2013Hansen et al 2012). Within this study, we examined the NDTs of forager bumblebees on artificial flowers with different combinations of radiating or non-radiating floral patterns of two modalities: visual and olfactory.…”
Section: Discussionmentioning
confidence: 99%
“…If this rate of pollination is consistent over several seasons, it would indicate that, as in many Cypripedium species, Batesian mimicry coupled with super normal stimuli works rather infrequently (Edens-Meier et al 2013, 2014. Kunze and Gumbert (2001) suggested that food deceptive orchids should be scentless, after experimentally demonstrating that bumblebees are less able to distinguish between artificial blue flowers with subtly different hues when scent is absent (also see Leonard et al, 2012). Therefore, in the absence of behavioural assays with known pollinators, we cannot yet determine whether the weak terpenoid floral scent of T. crinita serves any pollinator-related function.…”
Section: Discussionmentioning
confidence: 97%
“…Additionally, sensing the wind environment could enhance decision accuracy and speed about which types of flower contain rewards (Burns and Dyer, 2008;Mirwan and Kevan, 2015). This is analogous to the capacity of the bee brain to integrate both colour and olfactory information for reducing uncertainty in decision making (Leonard et al, 2011). Additionally, the association of wind with certain visual features could also aid in improving flight efficiency, for example by avoiding edges of objects in windy conditions where strong destabilizing jets and gusts can be detrimental to flight.…”
Section: Discussionmentioning
confidence: 99%
“…Honeybees trained in a Y-maze to solve complex delayed matching to sample problems in the visual domain can slowly learn this task, and then apply the acquired rule to solve a novel olfactory presentation of stimuli (Giurfa et al, 2001). Furthermore, bees have been shown to use visual and olfactory information in ecologically relevant foraging scenarios as scent can trigger memory for specific colours previously associated with rewarding stimuli (Leonard et al, 2011;Reinhard et al, 2004a;Srinivasan et al, 1998). This suggests that different modalities of sensation may potentially operate synergistically to enhance decision making.…”
Section: Introductionmentioning
confidence: 99%